Photothermal detection of trace compounds in water, using the deflection of a water meniscus - Hodgkinson, Jane; Johnson, Mark; Dakin, John P. (IOP Publishing, 1998)
A novel photothermal detector is described, based on a closed cell suitable for use with low-frequency modulated continuous-wave light sources. Photothermal expansion in aqueous samples caused the deflection of a water meniscus held across a 200μℳ radius pinhole. Displacement of the water meniscus was measured using fibre-optic interferometry. A mercury discharge lamp (254 nm) and a laser diode (678 nm) were used to detect absorption by 2 ppb anthracene and 0.5 ppm potassium permanganate in aqueous solutions, respectively. The technique was used to detect differences between absorption coefficients in aqueous solutions down to approximately 20% of the background absorption of the water itself.